2022
DOI: 10.3390/molecules27165344
|View full text |Cite
|
Sign up to set email alerts
|

The Genus Broussonetia: An Updated Review of Phytochemistry, Pharmacology and Applications

Abstract: The Broussonetia genus (Moraceae), recognized for its value in many Chinese traditional herbs, mainly includes Broussonetia papyrifera (L.) L’Hér. ex Vent. (BP), Broussonetia kazinoki Siebold (BK), and Broussonetia luzonica (Blanco) Bureau (BL). Hitherto, researchers have found 338 compounds isolated from BP, BK, and BL, which included flavonoids, polyphenols, phenylpropanoids, alkaloids, terpenoids, steroids, and others. Moreover, its active compounds and extracts have exhibited a variety of pharmacological e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 120 publications
0
8
1
Order By: Relevance
“…Thus, a small amount of BZ-EXT is sufficient for this sensing methodology. Yueru Chen et al mentioned the constituents present in Broussonetia species, [35] among which vitexin, [38] apigenin [39] etc. flavonoids, Dihydrosyringin [40] etc.…”
Section: Colorimetric Sensingmentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, a small amount of BZ-EXT is sufficient for this sensing methodology. Yueru Chen et al mentioned the constituents present in Broussonetia species, [35] among which vitexin, [38] apigenin [39] etc. flavonoids, Dihydrosyringin [40] etc.…”
Section: Colorimetric Sensingmentioning
confidence: 99%
“…[31] In another study, Ruimeng et al found that core-shell Cu/Au nanoparticles can be used to calorimetrically detect glucose and GSH. [32] K. S. Kumar et al used green synthesized Ag colloidal nanoparticles for the selective sensing of divalent Hg and H 2 O 2 . [33] Hany F. et al used the colorimetric sensing of alkaline vapors was achieved through color changes of the rhodamine B hydrazone-coated silica strips from pink to colorless or faded pink upon exposure to the vapors of the alkaline analytes at 0.1 μL.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations